دور الاتفاقيات الثنائية في تطوير العلاقات التجارية السورية – الروسية - عثمان سلمان; محمد زينه (Latakia University Journal - Economic and Legal Sciences Series, 2016)
Though of their huge natural resources and productions, states cannot reach self-sofficiency. So we find that countries tend to cooperate with each other according to certain conditions. They may become members in an international organizations to support trade and economy, or even each country may sign bilateral agreements with other countries. Recently, agreements like these have become very popular between countries and especially Syria, because of the advantages offered by those agreements, and there is no doubt that the swap’s benefits give to each state the opportunity to get some products that do not have either because of its climate conditions or natural abilities do not allow it to produce such goods. Production costs may exeed that of the imported ones. Through trading between countries, they can get different products and services. So the role of these agreements must be studied on the Syrian external trade generally and particulary Russian-Syrian because of its strong economic structure at first and good political relations secondly.Deep study on the role of these agreements between the two countries can ensure that these relations were not affected by the international developments, through the Syrian-Russian trade balance analysis of the role of these agreement on the reality of foreign trade between the two countries. Thos knowing the weakness in trade relations and how to overcome it. It also aims to enhance strength points to upgrade the Syrian foreign trade, which reflect positively on the various aspect of life. لا تستطيع الدول, مهما كانت غنية بمواردها الطبيعية وإنتاجها, أن تؤمن لمجتمعاتها الاكتفاء الذاتي، وبهذا نجد أن الدول تسعى للتعاون مع بعضها وفق شروط معينة. فقد تدخل في منظمات أو تكتلات دولية لدعم التجارة والاقتصاد، أو قد تقوم كل دولة بتوقيع اتفاقيات ثنائية مع دولة أخرى. وقد شاع في الفترة الأخيرة قيام مثل هذه الاتفاقيات بين الدول بشكل كبير وخصوصاً سورية، بسبب المزايا الكثيرة التي تقدمها هذه الاتفاقيات للدول، ولاشك أن لهذه المبادلة فوائدها، فهي تعطي لكل دولة الفرصة في الحصول على بعض المنتجات التي لا تتوفر لديها؛ إما لأن ظروفها المناخية أو إمكانياتها الطبيعية لا تسمح لها بإنتاجها، أو أنه إذا أمكن إنتاجها فإنها تنتجها بتكاليف تعلو على تكاليف المنتجات المستوردة، وهكذا تتمكن الدول المختلفة عن طريق الاتجار مع بعضها من الحصول على أنواع مختلفة من المنتجات والخدمات. لذلك لابد من دراسة دور هذه الاتفاقيات في التجارة الخارجية السورية عموماً والسورية الروسية خصوصاً, لما تتمتع به من هيكل اقتصادي قوي أولاً, ومن علاقات سياسية جيدة ثانياً, ما يضمن عدم تأثر هذه العلاقات بالمستجدات الدولية. وسنعمد إلى تحليل الميزان التجاري السوري الروسي, لبيان دور هذه الاتفاقيات على واقع التجارة الخارجية بين البلدين ثم معرفة نقاط الضعف في العلاقات التجارية بين البلدين وتجاوزها, وكذلك تعزيز نقاط القوة بقصد الارتقاء بالتجارة الخارجية السورية وتعزيزها بما ينعكس إيجاباً على مختلف جوانب الحياة.